THE EFFECTIVENESS OF HEALTH EDUCATION ON PARENT’S KNOWLEDGE LEVEL ABOUT CHILDREN WITH CONGENITAL TALIPES EQUINOVARUS IC ROOMS - Ingga; Amir, Yufitriana; Novayelinda, Riri (Universitas Karya Husada Semarang, 2025)
CTEV (Congenital et al.) is defined as a condition in which there is adductor in the front of the foot and supination in the back, varus in the toes in the subtalar complex, equinus in the hindfoot, and medial deviation of the entire foot towards the floor surface. The CTEV therapy process requires routine and periodic evaluations until the child ages 4-5. This, of course, impacts the level of knowledge and compliance of parents in accompanying their children during the therapy program. Examining how health education utilizing leaflet media affects parents' understanding of children with CTEV is the primary goal of this study. One group was given a pretest-posttest as part of this quantitative study's quasi-experimental methodology. The parents of children who are patients make up the population. Thirty participants were selected using a purposive sampling method. Using a questionnaire as its measuring instrument, this study examines two parts: part A, which focuses on respondent characteristics, and part B, which delves into questions on CTEV and the knowledge element associated with it. The analysis used is a bivariate analysis using the Wilcoxon test. There is a significant difference in the mean level of parental knowledge on the pre-test and post-test in the experimental group, with a p-value of 0f 0.019. Health education regarding CTEV for parents who have children suffering from CTEV using leaflets influences the level of knowledge of respondents. Hopefully, these results can be an alternative intervention to increase parents' knowledge about CTEV.